Harriet Tubman : Myth, Memory, and History - Sernett, Milton C., 1942- (Book collections on Project MUSE., 2007)
Harriet Tubman: Myth, Memory, and History tells the fascinating story of Harriet Tubman's life as an American icon. The distinguished historian Milton C. Sernett compares the larger-than-life symbolic Tubman with the actual "historical" Tubman. He does so not to diminish Tubman's achievements but rather to explore the interplay of history and myth in our national consciousness. Analyzing how the Tubman icon has changed over time, Sernett shows that the various constructions of the "Black Moses" reveal as much about their creators as they do about Tubman herself